2003
DOI: 10.1046/j.1525-1438.2003.13039.x
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine combined with cisplatin as first-line treatment in patients 60 years or older with epithelial ovarian cancer: a phase II study

Abstract: This phase II study evaluated the activity and toxicity of gemcitabine plus cisplatin as first-line treatment of patients with advanced ovarian cancer. Chemonaive patients >/=60-year-old with FIGO stage IIIC or IV epithelial ovarian carcinoma were enrolled. Patients received cisplatin 75 mg /m2 on day 1 and gemcitabine 1250 mg /m2 on day 1 (before cisplatin) and day 8 of a 21-day cycle. Of 44 female patients (median age, 70 years), 72.7% had stage IIIC disease and 67.4% had a Karnofsky performance status >/=80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…These results are promising when compared with a median overall survival rate of 36–39 months for subjects treated with paclitaxel/platinum‐containing chemotherapy as reported in a systemic review of three large studies, which included stage II cancer in addition to stage III and stage IV cancer 5 . More interestingly, our results are very similar to the experience of Bauknecht et al , who, in a phase II study with gemcitabine and cisplatin as first‐line treatment of people older than 60 years with FIGO stage IIIC or stage IV epithelial ovarian carcinoma, found an overall response rate of 62.2% (95% CI, 44.8–77.5%) and a median survival of 27.7 months (95% CI, 14.3–40.8 months) 18 . Also, Nogue et al reported a similar study with gemcitabine and cisplatin, with an overall clinical response rate of 70.7% (95% CI 56.8–84.6%), a median overall survival of 23.4 months (95% CI 15.9–29.9 months) and a median progression‐free survival time of 10.4 months (95% CI 9.4–13.5 months) 19 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are promising when compared with a median overall survival rate of 36–39 months for subjects treated with paclitaxel/platinum‐containing chemotherapy as reported in a systemic review of three large studies, which included stage II cancer in addition to stage III and stage IV cancer 5 . More interestingly, our results are very similar to the experience of Bauknecht et al , who, in a phase II study with gemcitabine and cisplatin as first‐line treatment of people older than 60 years with FIGO stage IIIC or stage IV epithelial ovarian carcinoma, found an overall response rate of 62.2% (95% CI, 44.8–77.5%) and a median survival of 27.7 months (95% CI, 14.3–40.8 months) 18 . Also, Nogue et al reported a similar study with gemcitabine and cisplatin, with an overall clinical response rate of 70.7% (95% CI 56.8–84.6%), a median overall survival of 23.4 months (95% CI 15.9–29.9 months) and a median progression‐free survival time of 10.4 months (95% CI 9.4–13.5 months) 19 .…”
Section: Discussionsupporting
confidence: 88%
“…5 More interestingly, our results are very similar to the experience of Bauknecht et al, who, in a phase II study with gemcitabine and cisplatin as first-line treatment of people older than 60 years with FIGO stage IIIC or stage IV epithelial ovarian carcinoma, found an overall response rate of 62.2% (95% CI, 44.8-77.5%) and a median survival of 27.7 months (95% CI, 14.3-40.8 months). 18 Also, Nogue et al reported a similar study with gemcitabine and cisplatin, with an overall clinical response rate of 70.7% (95% CI 56.8-84.6%), a median overall survival of 23.4 months (95% CI 15.9-29.9 months) and a median progression-free survival time of 10.4 months (95% CI 9.4-13.5 months). 19 In this respect, our study suggests that the combination of gemcitabine and carboplatin seems to be as efficacious as combined gemcitabine and cisplatin; in the same way, paclitaxel and carboplatin is equally efficacious as paclitaxel and cisplatin.…”
Section: Discussionmentioning
confidence: 83%
“…The synergy (10 -12) and clinical activity of systemic cisplatin and gemcitabine in patients with ovarian cancer are well described both in the chemotherapy-naive and relapse populations (13,14). Several characteristics of gemcitabine have suggested that it is a reasonable candidate for exploration in the i.p.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of gemcitabine to cisplatin may have synergistic tumoricidal activity even in women with platinum-resistant tumors. It is postulated that gemcitabine prevents DNA synthesis and repair and thus helps circumvent platinum resistance [11,12] Several studies have evaluated the combination gemcitabine and cisplatin (or carboplatin) among women with primary [13,14] and recurrent [2,[15][16][17][18][19][20][21][22] ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%